Rumen ciliate fauna of Icelandic cattle, sheep, goats and reindeer - FUENTE, GABRIEL D.L.; SKIRNISSON, K.; DEHORITY, BURK A. (Zootaxa, 2006)
Concentration and percentage generic and species composition were determined in rumen contents from five cows, five sheep, two goats and five reindeer living in Iceland. In general, total concentrations of ciliated protozoa in all species were similar to previously reported values. Concentrations of total protozoa ranged between 5.2 x 10 4 and 44.5 x 10 4 in the three domesticated species, as compared to a range of 130 x 10 4 – 250 x 10 4 in reindeer. Thirty-four species of protozoa plus 10 subspecies or forms were observed in Icelandic cattle, 27 species plus four forms were found in sheep, 13 species plus 2 forms in goats and 19 species in reindeer. Both Polyplastron and Ophryoscolex species were absent from all domestic animal species. However, this has been observed in a number of other geographical locations. The fauna present in reindeer was a typical rangifer-type fauna which is unique to that species and would further substantiate the occurrence of some host specificity in the genus Rangifer. It would appear that neither climate, nor isolation has markedly influenced protozoan populations in Iceland. . Key words: Cattle, ciliate protozoa, goats, Iceland, reindeer, rumen, sheep